The Influence of Motivation and Work Commitment on the Performance of State Civil Servants at the Deli Serdang Regency Land Office - Devi Susanto Sibagariang; Elisabet Siahaan; Hamdani Harahap (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to find out how much influence work motivation and commitment has on the performance of state civil servants at the Deli Serdang Regency Land Office. Sampling The samples used in this research were all state civil servants at the Deli Serdang Regency Land Office except the Head of the Deli Serdang Regency Land Office, so there were 92 people present. In this research, the data used is primary data, then continued with path analysis. The results of the analysis show that there is a positive and significant influence between motivation and performance. This means that better motivation can improve the performance of state civil servants at the Deli Serdang Regency Land Office. There is a positive and significant influence between work commitment and performance. This means that an increase in work commitment that is getting better can improve the performance of state civil servants at the Deli Serdang Regency Land Office. There is a positive and significant influence between motivation and work commitment on performance. This means that motivation which is interrelated with better work commitment can improve the performance of state civil servants at the Deli Serdang Regency Land Office.